Learning in a rich country: the normalisation of homelessness among apprentices in Australia. (13th September 2016) - Cebulla, Andreas
ABSTRACT: This paper documents evidence of a 'normalisation' of the risk of homelessness experienced by apprentices and trainees in Australia. It draws on a bespoke survey of past and current learners in its Southern state, group and one-to-one interviews with apprentices and trainees, and a review of a government support programme, conducted in 2012 and 2013. The research produced evidence of apprentices and trainees experiencing homelessness in the course of their studies, but also applying preventative strategies to avoid or lessen its impact. At the same time, the study encountered behaviours and judgements reflecting a generalised acceptance among learners and training providers of this risk, which has been reinforced by the marketisation of training provisions in Australia.